Life Threatening Severe QTc Prolongation in Patient with Systemic Lupus Erythematosus due to Hydroxychloroquine - John P. O’Laughlin; Parag H. Mehta; Brian C. Wong (Case Reports in Cardiology)
We present a case of a syncopal episode resulting from significant QT interval prolongation in a patient on hydroxychloroquine for the treatment of systemic lupus erythematosus and end stage renal disease. The patient had been treated with hydroxychloroquine for two years prior to presentation. After thorough workup for secondary causes of QT interval prolongation hydroxychloroquine was discontinued and the patient’s QT interval shortened. The patient was treated with mexiletine to prevent sudden ventricular arrhythmias, which was unique compared to other documented cases in which lidocaine was used. The patient was noted to have mild prolongation of the QT interval on electrocardiogram prior to initiation of hydroxychloroquine therapy which was exacerbated by its use and may have been caused due to toxicity from underlying renal failure.